Law Enforcement Problems Against Account Buying and Selling Cases in Money Laundering in Indonesia - Wahyu Sabrudin Sabrudin; Triono Eddy; Adi Mansar (Faculty of Law, Universitas Pekalongan, 2025)
There are many modes of money laundering with the aim of obscuring the origin of money from criminal acts so that the law is often lagging behind, regulating the dynamics of the modes that emerge, one of which is buying and selling accounts in money laundering crimes so that there are problems in law enforcement. The research method used is normative juridical. The results of the study show that the urgency of regulating the mode of buying and selling accounts for money laundering crimes can strengthen the law enforcement process.